Determination of the Sun Protection Factor (SPF) of Ethanol Extract Gel from Arumanis Mango Leaves (Mangifera indica L. var. arumanis) as a Sunscreen Using the UV-Vis Spectrophotometry Method - Laikhah; Indah Shaliha; Alif Warnandi (Jurnal Riset Kefarmasian Indonesia, 2026)
Skin damage caused by ultraviolet radiation has become a major health concern, prompting the search for natural photoprotective agents. This study aimed to determine the sun protection factor of ethanol-based Mangifera indica L. var. arumanis leaf extract and its topical gel formulations. Fresh mature leaves were dried, powdered, and extracted using maceration with 96% ethanol. The extract was subsequently formulated into gels with varying concentrations and evaluated for physical properties including pH, viscosity, spreadability, adhesion, homogeneity, and organoleptic characteristics. The sun protection factor was measured using UV-Visible spectrophotometry and calculated via the Mansur equation. Results showed that the ethanol extract provided ultra-level photoprotection at all tested concentrations, while gel formulations containing higher extract concentrations achieved enhanced sun protection, with optimal physical stability observed at intermediate concentrations. Excessive extract concentration resulted in reduced homogeneity and decreased adhesion. These findings demonstrate that Mangifera indica L. var. arumanis leaf extract is a promising natural sunscreen ingredient and that careful formulation is required to balance biological efficacy with physical stability. The study provides a basis for developing safe and effective natural sun protection products.